Economic evaluation for health advocacy and informed policy / Maznah Dahlui - Maznah , Dahlui (Universiti Malaya, 2018)
Globally, economic evaluation is gaining prominence as a potential tool for advocacy in health care programmes. Economic evaluations can inform decisions concerning the efficiency and allocation of resources to implementation strategies which are explicitly designed to inform care providers and patients about the best available research evidence and to enhance its use in their practices. These strategies are increasingly popular in health care, especially in light of growing concerns about quality of care and limits on resources. However, such concerns have hardly driven health authorities and other decision-makers to spend on some form of economic evaluation in their assessments of implementation strategies.